Liposomal nanosystems in rheumatoid arthritis - Ferreira-Silva, Margarida (2021)
This work received financial support from PT national funds from Fundacao para a Ciencia e Tecnologia (FCT) through the grant FCT/MEC (UID/DTP/04138/2020 and UIDP/04138/2020) financing Research Institute for Medicines-iMed. ULisboa, grant FCT/MEC (UIDP/04378/2020 and UIDB/04378/2020) financing Applied Molecular Biosciences Unit-UCIBIO, a grant by FCT/MCTES (UIDB/50006/2020) financing LAQV-REQUIMTE Associate Laboratory, from the European Union (FEDER funds through COMPETE POCI-01-0145-FEDER-029253), and by Phospholipid Research Center (project LCO-2017-052/1-1). M.F.-S. acknowledges PhD grant PD/BD/135,264/2017 attributed by the FCT i3DU PhD program.